Segmental zoster paresis - Shihab, Nahla; Pusponegoro, Erdina HD; Yanuar, Ahmad (Journal of General - Procedural Dermatology and Venereology Indonesia, 2017)
Herpes zoster is often associated with neurological manifestation but less frequently associated with motoric nerve involvement. The most common motoric involvement is paresis, seen only in 1-5% of all zoster cases. This case report a 39-year-old male, with recurrent abdominal liposarcoma under chemotherapy, presented with symptoms of fever, and painful and weak right leg for 2 weeks. Vesicles eruption was seen on his right leg nine days after these symptoms occurred. Physical examination revealed groups of haemorrhagic vesicles with erythematous base on the right lower leg. Lumbosacral spine x-ray showed spondylosis with radiculopathy. Electromyography (EMG) examination revealed lower motor neuron total denervation corresponding to right L5 radix. The patient was diagnosed as herpes zoster on right L5-S1 segment, herpetic neuralgia, and segmental zoster paresis with recurrent liposarcoma under chemotherapy. He was treated with oral acyclovir 800 mg five times a day and gabapentin 300 mg twice a day. Physical therapy and rehabilitation were started concurrently. Paresis is a rare complication of herpes zoster. Radicular pain and weakness preceded the skin lesion potentially lead to misdiagnoses. The most frequent diagnosis for patient suffering pain and weakness in the extremities is spinal disorder, such as stenosis and disc herniation. EMG can be helpful to recognise motoric involvement of herpes zoster, and preclude other diagnoses.